Peran Orangtua Tunggal Dalam Membentuk Nilai agama Anak Usia dini Di Samadua Kabupatrn Aceh Selatan - Yarzi - Napila; Heliati Fajriah; Munawwarah Munawwarah (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah UI BBC, 2023)
Single parents who raise children without a father or mother to accompany them require more struggles and challenges in raising and meeting family needs. The background of this research is that family education is very important, especially religious education, because religion is an asset for children as a provision for their next life, every parent ust instill it fro an early age. The subjects of this study were 3 single parents who had children aged 56 years in Mukim Sedar, Samadua District, South Adeh District. This study aims to determine the roles and constraints of single fathers and single mothers in shaping children’s religious values in Mukim Sedar, Samadua District, South Aceh District. This study uses qualitative research with a case study approach. Data collection techniques are observation, interviews and documentation. The mothers instill religious values in children by means of gentleness, affection, and communicate more verbally, on the other hand, fathers tend to be more assertive and don’t communicate much verbally with their children. The religious values fomed by the Samadua community for early childhood are faith, morals, and worship education. In addition, the constraints faced are limited time because parents work to meet family.